2022
DOI: 10.1007/s10479-022-04651-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impacts of COVID-19 outbreak on supply chain risks by modified failure mode and effects analysis: a case study in an automotive company

Abstract: Supply chains have been facing many disruptions due to natural and man-made disasters. Recently, the global pandemic caused by COVID-19 outbreak, has severely hit trade and investment worldwide. Companies around the world faced significant disruption in their supply chains. This study aims to explore the impacts of COVID-19 outbreak on supply chain risks (SCRs). Based on a comprehensive literature review on supply chain risk management, 70 risks are identified and listed in 7 categories including demand, suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 90 publications
1
10
0
1
Order By: Relevance
“…Focusing instead on the MEM industry, the available literature has provided some evidence on the automotive industry ( Tamtam and Tourabi, 2021 ; Ghadir et al, 2022 ), which is a very specific segment of this sector; hence, results of these previous studies are not always suitable for a direct comparison with the present paper. Having said that, it is first to be observed that the drop in the volumes handled for the MEM industry appears as less relevant compared to T&F. Similar considerations hold true for the service level delivered to customers: MEM companies suffered from poor service performance mainly at the very beginning of the pandemic period, corresponding to the lockdown of many countries, but the pre-Covid conditions were easily restored.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Focusing instead on the MEM industry, the available literature has provided some evidence on the automotive industry ( Tamtam and Tourabi, 2021 ; Ghadir et al, 2022 ), which is a very specific segment of this sector; hence, results of these previous studies are not always suitable for a direct comparison with the present paper. Having said that, it is first to be observed that the drop in the volumes handled for the MEM industry appears as less relevant compared to T&F. Similar considerations hold true for the service level delivered to customers: MEM companies suffered from poor service performance mainly at the very beginning of the pandemic period, corresponding to the lockdown of many countries, but the pre-Covid conditions were easily restored.…”
Section: Discussionmentioning
confidence: 92%
“…Two case studies in the fashion footwear context have been analyzed by Braglia et al (2022) , with the aim to investigate how companies in this field reacted to the disruption caused by the Covid-19 pandemic, so as to increase resilience in case of future disruptions. The papers by Tamtam and Tourabi (2021) and Ghadir et al (2022) have instead analyzed the effects of Covid-19 in the automotive industry. The former authors have focused on the agile capability of automotive companies in the pandemic period, while the latter authors have proposed an approach for prioritizing risks induced by Covid-19 in the automotive supply chain.…”
Section: Literature Analysismentioning
confidence: 99%
“…There has been high attention among researchers for performance management in the healthcare sector (Jiang et al, 2020 ). The increased competitive pressure of COVID-19 has forced hospitals to revise their evaluating management system (Ghadir et al, 2022 ; Lotfi, Kargar, Gharehbaghi, et al, 2021a ). There are several important issues for the hospital circular supply chain such as supply chain inefficiencies, redundant administrative costs, and unsuitable care, waste.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crisis management has become a key aspect of all organizations in recent years, particularly for multinational companies such as the one presented in this article. After worldwide cyberattacks such as Wannacry and Not Petya (Backman, 2021), worldwide terrorist threats (Ruggiero & Vos, 2015), the COVID‐19 global pandemic (Capano et al, 2020), and the Suez Canal disaster (Ramos et al, 2021), all organizations recognize that they are at risk of suffering the consequences of crises and must therefore be prepared, including companies (Branquinho, 2018; Dau et al, 2018; Ghadir et al, 2022; Li, 2022; Özkanlisoy & Akkartal, 2021; Rababah et al, 2020; Richardson et al, 2009; Watson et al, 2017). The first stage of such preparation is to set up a dedicated and organized group or cell within the organization that is responsible for managing and responding to crises or emergencies, called a crisis cell.…”
Section: Introductionmentioning
confidence: 99%